2015
DOI: 10.3109/23744235.2015.1123290
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in seroprevalence for herpesviruses among pregnant women in Finland: cross-sectional study of three time points 1992, 2002 and 2012

Abstract: Maternal herpesvirus infections during pregnancy may cause fetal and neonatal infections. We investigated the seroprevalence of five herpesviruses: cytomegalovirus (CMV), herpes simplex virus (HSV) 1 and 2, varicella zoster virus (VZV) and Epstein-Barr virus (EBV) in randomly selected samples from pregnant Finnish women from the years 1992, 2002 and 2012. Over 20 years, the seroprevalences decreased significantly for CMV from 84.5% to 71.5% (p = 0.007) and HSV-1 from 69.5% to 45% (p < 0.001). The decrease in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 29 publications
4
32
2
2
Order By: Relevance
“…Our cohort was well protected against varicella, which is in accordance with previous reports in the Finnish population [34].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our cohort was well protected against varicella, which is in accordance with previous reports in the Finnish population [34].…”
Section: Discussionsupporting
confidence: 81%
“…The sera were analyzed at HUSLAB with EIA techniques during fall 2015. Varicella IgG was measured using an inhouse VZV-IgG EIA test [18,19] Varicella, measles and mumps antibodies were defined positive or negative according to the manufacturer's guidelines. Rubella antibodies were considered non-protective when titers less than 15 EIU were detected.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…In Asia EBV seroprevalence rapidly increased with age, exceeding 80% by age 5, and 90% by 7-8 years [19,21,36,47]. In contrast, studies in Europe and North America showed a more gradual increase in seroprevalence which did not exceed 90% until age 22 [23,25,28,33,38,43,49,53,79,83]. Studies which used validated, commercially available tests for EBV antigens were more likely to show increases in seroprevalence with age than studies which used in-house tests or did not reported which test they used; these studies also tended to be larger and representative of the underlying population (Table S1 in the Online Supplementary Document).…”
Section: Age and Ebv Seroprevalencementioning
confidence: 96%
“…A study conducted in Japan [5] has shown that before the early 1990s, more than 80% of children aged 5 to 7 were found to be seropositive, whereas the positivity rate decreased to 59% for the years 1995–1999. In contrast, in Finland, EBV seroprevalence in pregnant women has remained unchanged in the last 20 years [6]. This age shift observed in some countries could lead to a higher incidence of symptomatic EBV PI, particularly of intense IM.…”
Section: Introductionmentioning
confidence: 99%